Exploring the Significance of Mecca Sacred Mosque Global Location - Wazeri, Yehia Hassan (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2017)
In traditional Islamic cities, the great mosque lies in the middle as the main landmark of the city. It is stated in the Qur'an that the Kaâ€™ba (Mecca sacred mosque) was the first house that was built in Mecca city for humanity to worship Allah. Therefore, Mecca is the holiest city of Islam, and the goal of the annual Muslim hajj (pilgrimage). The objective of the present study is to explore the significance of sacred mosque of Mecca global location on dry land by using accurate measurements and Satellite programs.The results of the study illustrate that the sacred mosque ofÂ Mecca equally distances away from the following locations:1) The farthest borders edges of Africa and Europe as well, 2) The nearest borders of the new world continents along with a part of Asia which meeting the Northern borders of North America at the Bering Sea, 3) The farthest borders of the new world continents that represent the outer edges of the dry land, 4) Finally, the Kaâ€™ba is equally distant from the geographical centers of the new world continents.